Pengukuran Kinerja dengan Metode Balanced Scorecard - Sidik Nurjaman (TRIKONOMIKA, 2013)
Measuring company performances using the Balanced Scorecard (BSC) is started by doing SWOT analysis to determine the internal and external factors. This analysis will show the company’s current position as well as the strategies that have to be applied. The results of the research shows that currently the company is in a good condition but facing a big challenge.Therefore the strategies that must be implemented is a strategy of diversification. The final step of this research is determining several KPI’s which generate six inisiative programs that must be done.They are conduct Focus Group Discussion with regular customers (wholesale and resellers), implement sales program references, doing pull marketing and targeted marketing programs, determining raw product completion time, conduct competency program design, conduct market surveis, do outreach company’s SOP to employees, to assess the ability of existing human resources, implement reward program for the achievement of the target, and build the competency profiles.